Adsorption of Arsenic, Lead, Cadmium, and Chromium Ions from Aqueous Solution Using a Protonated Chabazite: Preparation, Characterization, and Removal Mechanism - Laura Alejandra Pinedo-Torres; Adrián Bonilla-Petriciolet; María Elena García-Arreola; Yenetzi Villagrana-Pacheco; Ana G. Castañeda-Miranda; María Selene Berber-Mendoza (Adsorption Science & Technology)
The adsorption of As(V), Pb(II), Cd(II), and Cr(III) ions from aqueous solutions on natural and modified chabazite was studied. The functionalization of chabazite was performed via a protonation and calcination with the aim of generating Lewis acid sites to improve its anion exchange properties. The surface and physicochemical properties of both adsorbents were studied and compared. The adsorption isotherms of tested heavy metal ions were quantified and modeled to identify the best isotherm equation. Steric parameters for the adsorption of these ions were also calculated with a monolayer statistical physics model. Natural chabazite showed the maximum adsorption capacity for Pb(II), while the modified zeolite improved its As(V) properties in 79%. These results showed that the modified zeolite was able to remove both cations and anions from aqueous solution. The application of this functionalized chabazite can be extended for the removal of other anionic pollutants from water, thus opening the possibility of preparing new adsorbents with tailored properties for water treatment.